2013
DOI: 10.1007/s10803-012-1747-x
|View full text |Cite
|
Sign up to set email alerts
|

Real World Executive Control Impairments in Preschoolers with Autism Spectrum Disorders

Abstract: This study examined executive control (EC) in preschoolers with and without autism spectrum disorders (ASD) using the Behavior Rating Inventory of Executive Functions-Preschool Version (BRIEF-P). ASD participants were a clinically referred sample of preschoolers; the typically developing control group was selected from the BRIEF-P standardization sample. The ASD group was rated significantly worse on all BRIEF-P scores, and these impairments did not correlate with ASD symptoms. These findings document impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 41 publications
6
41
0
1
Order By: Relevance
“…The test developers argue for greater ecological validity for such reports over performance-based EF tasks to assess children across a variety of settings versus a laboratory or clinic (Isquith, Crawford, Espy, & Gioia, 2005). Furthermore, research has indicated that different clinical populations including children with ASD (Chan et al, 2009;Gilotty, Kenworthy, Sirian, Black, & Wagner, 2002;Semrud-Clikeman, Walkowiak, Wilkinson, & Butcher, 2010;Smithson et al, 2013), attention-deficit hyperactivity disorder (ADHD; Qian, Shuai, Cao, Chan, & Wang, 2010;Toplak, Bucciarelli, Jain, & Tannock, 2009), and frontal lesions (Jacobs, Harvey, & Anderson, 2007) obtain significantly elevated scores (i.e., indicative of EF deficit) on the BRIEF. Scores on the BRIEF Working Memory scale have also been associated with frontal-lobe gray-matter volume in typically developing children aged 5 to 17 years old (Mahone, Martin, Kates, Hay, & Horská, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The test developers argue for greater ecological validity for such reports over performance-based EF tasks to assess children across a variety of settings versus a laboratory or clinic (Isquith, Crawford, Espy, & Gioia, 2005). Furthermore, research has indicated that different clinical populations including children with ASD (Chan et al, 2009;Gilotty, Kenworthy, Sirian, Black, & Wagner, 2002;Semrud-Clikeman, Walkowiak, Wilkinson, & Butcher, 2010;Smithson et al, 2013), attention-deficit hyperactivity disorder (ADHD; Qian, Shuai, Cao, Chan, & Wang, 2010;Toplak, Bucciarelli, Jain, & Tannock, 2009), and frontal lesions (Jacobs, Harvey, & Anderson, 2007) obtain significantly elevated scores (i.e., indicative of EF deficit) on the BRIEF. Scores on the BRIEF Working Memory scale have also been associated with frontal-lobe gray-matter volume in typically developing children aged 5 to 17 years old (Mahone, Martin, Kates, Hay, & Horská, 2009).…”
mentioning
confidence: 99%
“…The preschool version (BRIEF-P) reportedly has a slightly different factor structure from the original BRIEF, with different scales loading on the three factors (Bonillo, Jiménez, Ballabriga, Capdevila, & Riera, 2012;Isquith, Gioia, & Espy, 2004). Further, for children with developmental disorders such as ASD and ADHD, most scales and indexes are elevated (e.g., Gioia, Isquith, Kenworthy, & Barton, 2002;Semrud-Clikeman et al, 2010;Smithson et al, 2013), thereby raising the question of whether the clinical scales provide useful profile information beyond the three indexes and the GEC. Finally, the developers of the BRIEF caution that the results need to be utilized in the context of other instruments such as performance-based measures (Isquith et al, 2005).…”
mentioning
confidence: 99%
“…All but three studies of EF in children younger than seven (Pellicano, 2007; Pellicano, Maybery, Durkin, & Maley, 2006; Smithson et al, 2013) are limited by the inclusion of children with ASD who also had general cognitive delays (e.g., Dawson et al, 1998, 2002; McEvoy, Rogers, & Pennington, 1993; Yerys, Hepburn, Pennington, & Rogers, 2007). Thus, although children with ASD are first distinguished from mental age matched typically developing and developmentally delayed children in inhibition, visual working memory and flexibility by preschool (Dawson et al, 1998; McEvoy et al, 1993), it is unclear whether EF difficulties are associated with ASD per se or the combination of ASD and cognitive delay.…”
mentioning
confidence: 99%
“…Dado que no existen baterías diseñadas específicamente para el TEA, las pruebas más utilizadas tanto en el ámbito de la investigación como en la práctica clínica, han sido la Torre de Hanoi, la Torre de Londres, la prueba de tarjetas de Wisconsin y el test de fluidez verbal, al igual que baterías como el Behavior Rating Inventory of Executive Function (BRIEF), entre otros (10,16,(21)(22)(23)(24)(25). En el presente estudio se decidió utilizar las subpruebas de función ejecutiva de la evaluación neuropsicológica Infantil (ENI) debido a que se trata de un instrumento validado para la aplicación en población colombiana entre 5 y 16 años (19).…”
Section: Discussionunclassified